2006
DOI: 10.1177/0145482x0610001106
|View full text |Cite
|
Sign up to set email alerts
|

Braille Literacy Skills: An Analysis of the Concept of Spelling

Abstract: This article analyzes the braille spelling errors of 16 Greek students who are blind. More specifically, it explores the types of spelling errors, the students’ attitudes toward spelling, and the relationship between spelling and reading strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
11

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 18 publications
2
21
0
11
Order By: Relevance
“…This appears to hold true in studies related to the education of low health literate individuals; Schwartzberg, Cowett, Vangeest, and Wolf (2007), for example, recently reported that drawing pictures was one of the most effective and underused techniques for educating low health literate individuals. However, the way in which vision is used to construe the world might create varied understandings of content in sighted persons versus those with VIs (Argyropoulos & Martos, 2006). In other words, the medium used to convey messages might create differences in how the messages are understood, which may affect how people with VIs understand health messages that are usually designed for and conveyed to sighted people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This appears to hold true in studies related to the education of low health literate individuals; Schwartzberg, Cowett, Vangeest, and Wolf (2007), for example, recently reported that drawing pictures was one of the most effective and underused techniques for educating low health literate individuals. However, the way in which vision is used to construe the world might create varied understandings of content in sighted persons versus those with VIs (Argyropoulos & Martos, 2006). In other words, the medium used to convey messages might create differences in how the messages are understood, which may affect how people with VIs understand health messages that are usually designed for and conveyed to sighted people.…”
Section: Discussionmentioning
confidence: 99%
“…Educators have long considered literacy a high priority for those with VIs (Argyropoulos & Martos, 2006; Rex, 1989). Literacy is a key skill for persons with VIs living in today’s world (Schroeder, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…It allows a great number of educational accommodations to be implemented -or at least to be piloted -and also constitutes an effective means of communication. However, little research has been done to document the parameters of the impact that computers and speech output software have on blind students' literacy skills (Argyropoulos and Martos, 2006). These studies need to increase and be extended in the area of comprehension to draw reliable inferences regarding the effectiveness of the various auditory manipulations.…”
Section: Discussionmentioning
confidence: 99%
“…Em pesquisa específica acerca do desenvolvimento da escrita ortográfica em crianças deficientes visuais, Arter e Mason (1994) pontuaram a importância do aprendizado da ortografia por meio de atividades que visem a reflexão acerca da língua escrita. Adicionalmente, grande relevância é atribuída ao domínio ortográfico pelos próprios jovens cegos (Argyropoulos & Martos, 2006), tanto para a sua inserção no ambiente escolar quanto para facilitar a comunicação escrita. Segundo Argyropoulos e Martos (2006), os jovens apontam ainda o domínio da ortografia como uma das qualificações mais básicas para o ingresso no mercado de trabalho.…”
Section: Considerações Finaisunclassified